COMPARISON OF PEDIATRIC INDEX OF MORTALITY (PIM)-3 AND PEDIATRIC SEQUENTIAL ORGAN FAILURE ASSESSMENT (pSOFA) SCORES TO PREDICT MORTALITY IN PEDIATRIC INTENSIVE CARE UNIT - PAWAR, ANKIT KUMAR; PRAJAPATI, GAURAV KUMAR; CHOUBEY, KANCHAN; RANDA, RASHMI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to evaluate and compare the pediatric index of mortality (PIM)-3 and pediatric sequential organ failure assessment (pSOFA) scores to predict mortality in pediatric intensive care unit (PICU). Methods: This cross-sectional study was conducted prospectively in PICU over 1 year. All consecutive patients admitted to the PICU aged 1 month to 12 years on designated study days were enrolled in the study (n=400). Mortality scores were calculated on the same day of admission using an Android calculator application. Results: The mean PIM-3 score in the non-survivor group (n=48) was higher, i.e., −0.81 (−2.05 to −0.44) than in the survivor group (n=352), i.e., −4.67 (−5.83 to −4.05) with p<0.001. The pSOFA score was also found higher in the non-survivor group, i.e., 11 interquartile range (IQR) (8–11) as compared to the survivor group, i.e., 3 IQR (2–5) with statistically significant difference (p<0.001). The median value of sensitivity and specificity for PIM-3 was reported to be 97.46% and 86.67%, respectively. The median value of sensitivity and specificity for pSOFA was 97.72% and 85.11%, respectively. The area under-receiver operating characteristic (AU-ROC) 0.9145 (95% confidence interval [CI]: 0.8595–0.9695) for the PIM-3 was almost equal to the AU-ROC of pSOFA score, i.e., 0.9554 (95% CI: 0.918–0.992). Both scores were positively associated with each other (r=0.807, <0.0001) Conclusion: Both PIM-3 and pSOFA scores were effective in predicting mortality in critically ill children.